1994
DOI: 10.1007/bf01221030
|View full text |Cite
|
Sign up to set email alerts
|

The chemosensitizer cyclosporin A enhances the toxic side-effects of doxorubicin in the rat

Abstract: Abstract:The feasibility of using chemosensitizers in the circumvention of P-glycoprotein-mediated multidrug resistance has been shown in many studies. We recently reported on the chemosensitizing effect of cyclosporin A (CsA) on doxorubicin in a rat solid tumour model. Using the same experimental design we investigated the side-effects of the combination treatment. During the 35-day experiment doxorubicin treatment caused dose-dependent weight loss, which was enhanced by combination treatment with CsA. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…The fact that combination treatment resulted in a small enhancement of toxicity in one experiment, as measured by body-weight loss, suggests that at least some systemic enhancement of epidoxorubicin activity may have occurred. This is in agreement with previous studies that showed enhancement of doxorubicin toxicity caused by combined treatment with cyclosporin A ( Van de Vrie et al 1994). Other investigators, however, have also furnished evidence for a direct effect of chemosensitizers on the tumour.…”
Section: Discussionsupporting
confidence: 94%
“…The fact that combination treatment resulted in a small enhancement of toxicity in one experiment, as measured by body-weight loss, suggests that at least some systemic enhancement of epidoxorubicin activity may have occurred. This is in agreement with previous studies that showed enhancement of doxorubicin toxicity caused by combined treatment with cyclosporin A ( Van de Vrie et al 1994). Other investigators, however, have also furnished evidence for a direct effect of chemosensitizers on the tumour.…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, considering that kidney can concentrate CSA up to 8 times the blood levels, our results suggest that ABCB1 activity in renal cells could be inhibited during CSA treatment, supporting the hypothesis that CSA-induced nephrotoxicity is, at least in part, due to ABCB1 inhibition. Indeed, we have previously shown that CSA increased sensitivity of Ma104 cells to the chemotherapeutic drug vincristine [10]and there are several reports of harmful interactions between CSA and other ABCB1 substrates, either exogenous or endogenous, in animals and humans [10, 24, 25, 26, 27]. Moreover, the observation that CSA increases ABCB1 expression in the proximal tubule of animals and humans [9, 12]and, that ABCB1 expression was unmodified in patients with CSA-induced nephrotoxicity [13], corroborate with the assumption that CSA-induced nephrotoxicity is related to ABCB1.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports of harmful interactions between CSA and other endogenous and exogenous ABCB1 substrates, in animals and humans [23, 24, 25, 26, 27]and, due to the importance of drug interactions for kidney integrity, it is of interest to understand how CSA affects intracellular accumulation of drugs in renal cells and whether this enhanced accumulation may contribute to CSA-induced nephrotoxicity. The divergences observed in the literature may be due to different experimental conditions and different cell lines used.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous in vitro studies have shown the ability of various types of agents to reverse resistance to anti-cancer agents of the MDR family. Relatively few studies using established solid tumours have been reported in experimental animals and no increase of therapeutic index was observed in these studies (Van de Vrie et al, 1994;Arvelo et al, 1995). Despite the limited evidence of benefit from animal models, there has been a substantial number of clinical trials that have evaluated the ability to reverse clinical drug resistance due to MDR.…”
Section: Discussionmentioning
confidence: 99%
“…Minimal experimentation using established solid tumours in animal models has been reported. Some solid tumour models have shown minor enhancement of anti-tumour effects when a reversing agent was given with an MDR drug but increased toxicity was observed and there were no therapeutic benefits (Van de Vrie et al, 1994;Arvelo et al, 1995). Several clinical studies to investigate the efficacy of P-gp reversal agents have been undertaken both in haematological malignancies and solid tumours.…”
mentioning
confidence: 99%